Role of NK cells in immunotherapy and virotherapy of solid tumors. (August 2015) - Cantoni, Claudia; Grauwet, Korneel; Pietra, Gabriella; Parodi, Monica; Mingari, Maria Cristina; Maria, Andrea De; Favoreel, Herman; Vitale, Massimo
Although natural killer (NK) cells are endowed with powerful cytolytic activity against cancer cells, their role in different therapies against solid tumors has not yet been fully elucidated. Their interactions with various elements of the tumor microenvironment as well as their possible effects in contributing to and/or limiting oncolytic virotherapy render this potential immunotherapeutic tool still difficult to exploit at the bedside. Here, we will review the current literature with the aim of providing new hints to manage this powerful cell type in future innovative therapies, such as the use of NK cells in combination with new cytokines, specific mAbs (inducing ADCC), Tyr-Kinase inhibitors, immunomodulatory drugs and/or the design of oncolytic viruses aimed at optimizing the effect of NK cells in virotherapy.